A Dualistic Concept of Personal Guarantee Responsibility and Its Relevancy with Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligation A Dualism Of Personal Guarantee Responsibility In Indonesia Bankruptcy Law - Liza Mashita Ramadhania (IHSA Institute, 2023)
Indonesia's legal system recognizes the concept of personal guarantee, which is a promise or guarantee of an individual as a third party to fulfil the debtor's obligations. The concept of guarantee in Indonesia regulates the roles and responsibilities of personal guarantees if the debtor cannot pay his debts. However, the problem is a dualism in theory or approach to personal guarantee responsibility, especially in carrying out debt collection in the debt settlement process in Bankruptcy and Suspension of Debt Payment Obligations (